The Making of Many Books : Printed Works on Ecclesiastes 1523-1875 - Weeks, Stuart (Book collections on Project MUSE., 2021)
Taking advantage of the unprecedented access to books and information that has become available in the last few years, this bibliography identifies and traces the history of hundreds of books and articles on Ecclesiastes published in many different languages before 1875. It includes not just scholarly literature but exegetical sermons, homiletic works, and poetic paraphrases of the text in order to offer significantly more comprehensive coverage than in any earlier bibliography. The publication history of each work is outlined in detail, with brief discussions of the background or content where appropriate, cross-references are given to major bibliographies and bibliographical databases, and indexes of authors, publishers, and biblical references are provided. Intended to serve as an important resource not only for students of Ecclesiastes and for bibliographers but for all who are interested in the history of reception or interpretation of the Bible, this bibliography also includes coverage of many more general works on the Megillot, on the Old Testament, and on the Bible as a whole in this period.